Zuhud Practice among ASN Ministry of Religion Tanjungbalai City - Hasnah Nasution; Al-Ahyu; Muzakkir; Abrar M. Dawud Faza (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This paper deals with Zuhud Practice among ASN Ministry of Religion Tanjungbalai City. Zuhud in Islam appeared at the time of the Prophet Muhammad and his companions which was reflected in the form of behavior. The author places zuhud on the second criticism, namely the practice of zuhud in the context of modern life which is influenced by the economic, social, cultural, scientific and so on. This research uses qualitative research by conducting field research and supplemented with library research. The research approach is a sociological approach and constructivism. The sociological and constructivist approach is carried out by observing the zuhud activity in religious policies in public spaces carried out by ASN (State Civil Apparatus) at the Office of the Ministry of Religion of TanjungBalai City in their daily social life. Based on the classification of zuhud, it can be stated that with zuhud a person can control himself from unlawful acts. That is the level of zuhud of ordinary people. If a person is able to live a zuhud lifestyle, then he will not commit corruption even though the opportunity is possible because his heart is filled with love and Allah's supervision of him. Leaving things that are forbidden requires people to seek wealth sincerely through hard work, and professionals who will prevent them from bribery, manipulation, corruption, oppressing the weak and so on. So that its existence will provide peace and happiness for others and the environment.